EP 49. Complications in impulse generator exchange surgery for deep brain stimulation: A single center, retrospective study. Issue 9 (September 2016) - Helmers, A.-K.; Witt, K.; Mehdorn, H.-M.; Lübbing, I.; Deuschl, G.; Synowitz, M.; Falk, D.
Abstract : Question: Low or empty battery status of non-rechargeable deep brain stimulation impuls generators (IG) requires a surgical IG exchange several years after initial implantation. Complications in patients undergoing DBS-Surgery are reported in the range between 7.6% and 25.3%. The aim of this study was to investigate the rate of complications after IG changes and to identify risk factors for complications. Methods: We retrospectively analyzed the complications in IG change surgery from 2008 to 2015 in a single center university hospital setting. Medical reports from all patients, who had undergone IG exchange surgery were systematically reviewed. The shortest follow-up was 2 months. Results: From 2008 to 2015, 438 generators were exchanged in 319 patients. Overall complication rate and revision rate was 8.9% of cases. 13 patients (2.96%) developed an infection of the IG with a secondary removal of the IG. Five patients (1.14%) suffered from local wound erosions surrounding the IG; for this particular complication in one patient the IG had to be removed while in the other 4 patients a local wound revision was sufficient. We found hardware malfunctions in 11 patients (2.51%) and local hemorrhage surrounding the IG in three cases (0.68%) requiring surgical revision. In two patients (0.46%) the IG needed to be refixated. In two patients (0.46%) tension of the connecting cables triggered a surgical revision because of patient's discomfort. One 80 years patient (0.23%) suffered from worsened severe heart failure and died 4 days after IG exchange in local anesthesia. In two cases (0.46%) the IG was placed abdominally or changed to a smaller device due to patient discomfort from initial positioning. Conclusion: IG exchange surgery, although often considered a "minor surgery", is associated with a complication rate of roughly 9% in our center. Infection is the most relevant complication as it causes removal of the IG. The implantation of smaller IGs might reduce complications such as wound erosions or local hemorrhages. Patients and physicians should know the rate of complication in IG exchange surgery since this information might facilitate a decision in favor of a rechargeable IG.